2020
DOI: 10.1186/s13071-020-04081-7
|View full text |Cite
|
Sign up to set email alerts
|

Latest trends in Leishmania infantum infection in dogs in Spain, Part I: mapped seroprevalence and sand fly distributions

Abstract: Background: This report describes L. infantum infection seroprevalence in dogs in Spain through data obtained from peer-reviewed literature and a cross-sectional serological survey assessing epidemiological and habitat variables as risk factors for infection. The study also provides preliminary sand fly species distribution data and indicates factors affecting their distribution and density.Methods: Three different studies were conducted in Spain: (i) a peer-reviewed literature seroprevalence survey ; (ii) a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 40 publications
5
73
2
9
Order By: Relevance
“…The cumulative incidence during these 24 years of observation was higher than previously reported in analysis of the same database (0.33 per 100,000 inhabitants between 1997 and 2014) ( 33 ) but lower than the reported incidence of Spain ( 16 , 25 ). After the modification of the confirmation and surveillance system ( 28 , 29 ), there was a significant increase of the total incidence probably due to an improved reporting, and because a possible increase in the clinical suspicion at primary care level.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The cumulative incidence during these 24 years of observation was higher than previously reported in analysis of the same database (0.33 per 100,000 inhabitants between 1997 and 2014) ( 33 ) but lower than the reported incidence of Spain ( 16 , 25 ). After the modification of the confirmation and surveillance system ( 28 , 29 ), there was a significant increase of the total incidence probably due to an improved reporting, and because a possible increase in the clinical suspicion at primary care level.…”
Section: Discussioncontrasting
confidence: 60%
“…Studies in different areas of Spain have reported seroprevalence varying from 4 to 35% in dogs, with a high proportion of them not showing any clinical signs of leishmaniasis ( 24 , 25 ). Phlebotomus perniciosus and Phlebotomus ariasi are the main vectors of Leishmania infantum in the Iberian Peninsula ( 23 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in different areas of Spain have reported seroprevalence varying from 4 to 35% in dogs, with a high proportion of them not showing any clinical signs of leishmaniasis (24,25). Phlebotomus perniciosus and Phlebotomus ariasi are the main vectors of Leishmania infantum in the Iberian Peninsula (23,26).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Spain, leishmaniasis is a hypoendemic, mandatory notifiable disease since 1995 (27), but reporting is compulsory for every Autonomous Region (CCAA) through the National Surveillance Network since 2015 (28). During the 2005-2017 period, Spain had an incidence rate of 0.62 cases per 100,000 inhabitants (16,25), with a heterogeneous distribution, mainly affecting the Mediterranean region (the Valencian Community, Catalonia, the Balearic Islands and Andalusia), except for the Community of Madrid, where a large community outbreak was identified in 2009 and 2010 linked to a newly identified reservoir (26). The objective of this study is to characterize the epidemiology and temporal trends in the incidence of human leishmaniasis in the city of Barcelona, between the years 1996 and 2019.…”
Section: Introductionmentioning
confidence: 99%